Uralic mythology and folklore - Hoppál, Mihály; Pentikäinen, Juha (Budapest : Ethnographic Institute of the Hungarian Academy of Sciences, 1968)
Een academisch werk over de volkeren in het hoge Noorden: hun wereldvisie, hun mythen, hun geloof, het sjamanisme, hun folklore, hun sociale leven, ...
Keywords: Folklore -- Estonia; Folklore -- Finland; Folklore -- Hungary